2020
DOI: 10.3390/genes11020156
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Circadian Clock and Regulators of Heat Stress Responses in Plants

Abstract: The circadian clock is found ubiquitously in nature, and helps organisms coordinate internal biological processes with environmental cues that inform the time of the day or year. Both temperature stress and the clock affect many important biological processes in plants. Specifically, clock-controlled gene regulation and growth are impacted by a compromised clock or heat stress. The interactions linking these two regulatory pathways include several rhythmic transcription factors that are important for coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…For instance, HS elicits morphological injuries, usually expressed as reduced growth, improper development and leaf senescence (Hasanuzzaman et al ., 2013; Nadeem et al ., 2018). At the physiological level, HS impacts photosynthesis, respiration and membrane plasticity (Hu et al ., 2020), affecting several genes/gene families such as those related to carbohydrate and amino acid metabolism (Liu et al ., 2016; Mazzeo et al ., 2018), hormone production and/or genes related to the circadian clock (Mody et al ., 2020). At the cell level, plant response to HS induces variation of the expression of hundreds of genes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, HS elicits morphological injuries, usually expressed as reduced growth, improper development and leaf senescence (Hasanuzzaman et al ., 2013; Nadeem et al ., 2018). At the physiological level, HS impacts photosynthesis, respiration and membrane plasticity (Hu et al ., 2020), affecting several genes/gene families such as those related to carbohydrate and amino acid metabolism (Liu et al ., 2016; Mazzeo et al ., 2018), hormone production and/or genes related to the circadian clock (Mody et al ., 2020). At the cell level, plant response to HS induces variation of the expression of hundreds of genes.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, considerable evidence links the circadian clock to both biotic and abiotic stress responses [ 12 , 159 , 160 ]. Clock function modulates responses to multiple stresses and, reciprocally, stresses modulate clock function, e.g., [ 161 , 162 , 163 , 164 , 165 , 166 ]. This reciprocal relationship extends to crops: the circadian clock modulates the drought response in poplar [ 167 ] and in B. rapa [ 168 ].…”
Section: Circadian Clock Components As Domestication and Crop Imprmentioning
confidence: 99%
“…The temporal effects of thermal stress during the plant’s life cycle and the diurnal cycle are critical, and plants have mechanisms to sense peak periods of stress and exhibit appropriate adaptive strategies. Recently, it has been reported that high temperature stress can influence plants’ biological clocks, which affects genes associated with the plant’s time sensing mechanisms [ 265 ]. Wu et al [ 266 ] reported the association of PePIF3a, a positive regulator in plants’ drought and salt stress responses, with circadian rhythms.…”
Section: Mechanisms Associated With Stress Tolerancementioning
confidence: 99%